Hubungan Dukungan Sosial dan Kencenderungan Kepribadian Ekstrovert dengan Kesejahteraan Psikologis pada Siswa SMA Negeri 1 Binjai - Endah Prita; Abdul Munir; Hasanuddin Hasanuddin (Universitas Medan Area, 2021)
This study aims to determine the relationship between Self Efficacy and the Role of Peers with Cheating Behavior in Students of SMA Negeri 1 Labuhan Deli. This study uses a correlational quantitative approach. The population in this study were 125 students who had a tendency to cheat who had previously been selected by screening. Samples were taken using the total sampling technique as many as 125 students. Data were analyzed using multiple regression formulas. This study uses a scale with the instrument of Self Efficacy, the role of peers and cheating behavior. The results showed: a) there was a significant negative relationship between Self Efficacy and cheating behavior in students, indicated by the correlation coefficient (rx1y) = -0.220; p = 0.048 0.05. b) there is a significant negative relationship between the role of peers and cheating behavior in students, indicated by the correlation coefficient (rx2y) = -0.226; p= 0.039 0.05. c) a significant negative relationship between self-efficacy, the role of peers and students' cheating behavior, as shown by the correlation coefficient (R) = -0.285; p = 0.006 0.05; Freg of 5.382, it can be concluded that the variables of Self Efficacy and the role of peers are related to cheating behavior. Thus, it can be stated that the hypothesis proposed in this study is accepted.